Analisa Tingkat Kenyamanan Pejalan Kaki Di Kota Tomohon - Mamuaja, Denny M. A.; Rompis, Semuel Y. R.; Timboeleng, James A. (Sam Ratulangi University, 2018)
Tomohon City is one of the cities in North Sulawesi Province, Indonesia. Before 2003 was one of the subdistricts in Minahasa District. In his development, Tomohon experienced a lot of progress, so there is aspiration of its citizens to improve the status of Tomohon into a city. Tomohon became an autonomous region (city) with the enactment of Law Number 10 Year 2003 regarding the Establishment of South Minahasa Regency and Tomohon City in North Sulawesi Province by DPR RI, but the inauguration was only on August 4, 2003. To support the activity and development of Tomohon City needed infrastructure physically and non-physically available so as not to inhibit the process. Physical infrastructure that includes facilities and infrastructure, use, design, etc. and non-physical include social relations, economic activity, etc. The need for physical infrastructure is essential to support the accessibility of urban activities and developments. The pedestrian lanes should be used only for pedestrian activity, not other activities such asvehicle activity and vehicle parking, trade because it can endanger safety and reduce the comfort of pedestrian circulation. Planning for pedestrian track requirements should be well planned in accordance with the rules andregulations of pedestrian path planning by considering and prioritizing safety and comfort aspects of pedestrians. Another factor that is often added as a support for comfort is physical comfort. Physical comfort is closely related to the aspect of the suitability of the shape and the design of the objects or elements built into thesurrounding environment, such as the suitability of park benches, garden lights, pedestrian paths, billboards and other infrastructure. Physical comfort is often associated with the concept of